Access to gifted education among African-American and Latino males. Issue 3 (13th August 2018) - Vega, Desireé; Moore III, James L.
Abstract : Purpose: Across the nation, African-American and Latino males have experienced limited access to placement in gifted education programs. This paper aims to pinpoint and describe the factors that frequently influence access to gifted education programming among African-American and Latino males. Design/methodology/approach: African-American and Latino males are persistently underrepresented in gifted education for reasons such as teachers' narrow conceptions of giftedness, teachers' bias in the nomination process and teachers' inappropriate usage and interpretation of intelligence measures. When these students qualify for such services, they often experience feelings of isolation and loneliness due to scarce representation of other African-American and Latino male students. A review of extant literature was conducted to identify factors that influence access to gifted education programming among African-American and Latino males. Findings: African-American and Latino males encounter roadblocks in being identified for gifted placement and many also experience implicit biases and stereotypical beliefs about their ability. The need for culturally competent professionals is critical to meet the academic and social-emotional needs of gifted African-American and Latino males. Practical implications: Recommendations for school psychologists and school counselors are offered to support the needs of gifted African-American and Latino males, assist in increasing their identification and participation in gifted education, and promote academic success. Originality/value: There is an urgent need for research on access and placement in gifted programming among African-American and Latino males. Moreover, the role of school psychologists and school counselors should be considered in facilitation of gifted identification and placement.